Answer:
see below
Explanation:
a The pythagorean theorem is a^2 + b^2 = c^2 where a and b are the legs and c is the hypotenuse
a^2 + b^2 = c^2
(6x+9y)^2 + (8x+12y)^2 = (10x + 15y)^2
b solve
(6x+9y)^2 + (8x+12y)^2 = (10x + 15y)^2
(6x+9y)(6x+9y) + (8x+12y)(8x+12y) = (10x + 15y)(10x+15y)
Factor out the common factors
3(2x+3y)3(2x+3y) + 4(2x+3y)4(2x+3y) = 5(2x+3y)5(2x+3y)
Rearrange
9 (2x+3y)^2 +16 (2x+3y)^2 = 25(2x+3y)^2
Divide each side by(2x+3y)^2
9 (2x+3y)^2/ (2x+3y)^2 +16 (2x+3y)^2/(2x+3y)^2 = 25(2x+3y)^2/(2x+3y)^2
9 + 16 = 25
25=25
This is true, so it is an identity